2016
DOI: 10.1007/s00520-016-3319-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cancer and quality of life among long-term survivors of breast cancer in Austria

Abstract: Long-term survivors of breast cancer in Austria perceive both positive and negative impacts of breast cancer. These perceptions, in particular the negative impact of cancer, appear to influence, or are potentially influenced by, physical and mental health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
5
23
0
Order By: Relevance
“…Similar results on the longterm impairment in QoL and HRQoL have been previously reported, although they have been somewhat conflicting (6)(7)(8)(9)(24)(25)(26)(27)(28). Several studies have revealed that especially i) sleep (6,7,24,27), ii) cognitive function (6,8,24,(27)(28), iii) fatigue (6,7,27), iv) emotional functioning (6,7,9,26) and v) mental health (6,9,27,29) remain impaired years after diagnosis and treatment. In our study, the BCS were worse off compared to the general population on the dimensions of i) sleeping, ii) excretion, iii) mental function, and iv) sexual activity still five years after treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results on the longterm impairment in QoL and HRQoL have been previously reported, although they have been somewhat conflicting (6)(7)(8)(9)(24)(25)(26)(27)(28). Several studies have revealed that especially i) sleep (6,7,24,27), ii) cognitive function (6,8,24,(27)(28), iii) fatigue (6,7,27), iv) emotional functioning (6,7,9,26) and v) mental health (6,9,27,29) remain impaired years after diagnosis and treatment. In our study, the BCS were worse off compared to the general population on the dimensions of i) sleeping, ii) excretion, iii) mental function, and iv) sexual activity still five years after treatment.…”
Section: Discussionsupporting
confidence: 69%
“…In particular, life interference associated with both QoL dimensions, the Meaning of cancer and body image concerns associated with physical functioning, and appearance concerns associated with mental functioning. Since the eight IOC‐V2 subscales, rather than the two summary scores, were used as regressors, our findings reinforce and expand the findings of Bouskill (), who reported that the positive impact of cancer associated with improved physical functioning, while the negative impact of cancer associated with poorer physical and mental functioning in long‐term survivors. In addition, our results expand other studies that demonstrated the influence of psychosocial aspects on long‐term cancer survivors’ QoL (e.g., Annunziata et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The state of having cancer, or having had the disease, has a wide range of psychological impacts, both negative and positive, that seem to be related to QoL (Bouskill, ; Crespi, Ganz, Petersen, Castillo, & Caan, ; Crespi, Smith, Petersen, Zimmerman, & Ganz, ; Oerlemans et al, ; Sarker et al, ; Smith, Crespi, Petersen, Zimmerman, & Ganz, ). Negative impacts include uncertainty and concern for the future and for one's own health (including the possibility of getting sick again), worries about one's body strength and functionality and the impossibility of returning to pre‐disease conditions, concerns about body image, and the interference of the disease on one's past, present and future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey is a widely used health survey which has been used extensively in breast cancer survivors [7379]. It includes 36 items covering eight health domains: physical functioning, bodily pain, role limitations due to physical health problems, role limitations due to personal or emotional problems, emotional well-being, social functioning, energy/fatigue, and general health perceptions.…”
Section: Methodsmentioning
confidence: 99%